Analisis Kepuasan Pengguna Website Parto.id Menggunakan Metode Webqual 4.0 - Hastuti, Meidya; Dodo Zaenal Abidin; Beni Purnama (LPPM Universitas Dinamika Bangsa, 2025)
In the digital era, the existence of a web-based information system is one of the important needs for local governments in providing services to the community. Information systems can also play a role in helping to improve operational efficiency, support business innovation, and accelerate decision making. One of the applications of the information system is the Parto.id website. Parto.id is a marketplace based on Business to Government (B2G) and Business to Business (B2B) which facilitates the implementation of e-purchasing of Procurement of Goods and Services whose main users are the government. The phenomenon of excessive purchasing on the Parto.id website in the Jambi Provincial Regional Government Organization environment can cause various significant problems. One of them is the waste of regional budget, especially if the purchase is not fully in accordance with the needs or its use is not optimal. This study aims to analyze the factors that influence user satisfaction and identify the obstacles experienced by users based on the dimensions of webqual 4.0. The focus variables measured include Usability, Information Quality, Service Interaction Quality and User Satisfaction. for Data collection is done by questionnaire, then the validity and reliability test of the data will be carried out, as well as the Hypothesis test using SmartPLS 4. The results of the study show that the website used is said to be very good with the value of the R-Square correlation of the User Satisfaction variable of 96.1%.